3(-2-6)=

Simple and best practice solution for 3(-2-6)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(-2-6)= equation:


3(-2-6)=0

We simplify the equation to the form, which is simple to understand
3(-2-6)=0

Reorder the terms in parentheses
+(-24)=0

Remove unnecessary parentheses
-24=0

We move all terms containing to the left and all other terms to the right.
0=0+24

We simplify left and right side of the equation.
0=+24

0=24

The left and right sides are not equal, therefore there is no solution. This equation is invalid.

See similar equations:

| 49-14=5(x-6) | | (2u-5)(6+u)=0 | | x+24+4x=-22-4x-26 | | -1/4x=21/4 | | (15x+7y)+(48x+25y)= | | 7-3(x-1)=2x | | an=-6n+10 | | x+1/2=0.98 | | -16t^2+20t+4=0 | | z/10-4=10 | | -1/X=0 | | a^2+21a-540=0 | | (45x+54y)+(-2x+33y)= | | 4x-2/2=-3 | | -u/12=12 | | -7+|-5|= | | x-0.08x=1700 | | 18+6x-12=-8-4x+9x | | (9x^(1/2))^2 | | 14z-7/7 | | 2*B+3*A=5 | | (14x-27y)+(32x+65y)= | | 5/6x^2*3/6x^2 | | 3(x-4)=12x-4-9x | | 2x^3-15x^2+24x+12=0 | | (50x-8y)+(32x+37y)= | | 24+x=-18 | | -3x^2-12x+1=0 | | 28=w(2w-1) | | (x-2)(x+4)=14 | | x^2+x-36= | | 12c+5=c+31 |

Equations solver categories